REGULASI TEKNIS PEMBUKTIAN PADA PELAKU INSIDER TRADING DALAM PASAR MODAL DI INDONESIA - Komang Dhira Pannavira (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2023)
This study aims to determine investor protection against insider trading in the Indonesian capital market and to find out the technical arrangements for proving insider trading in the Indonesian capital market. The method used in research related to the legality of medical cannabis as a treatment for cerebral palsy in Indonesia uses a type of normative juridical research, using a statutory approach or statute approach to analyze legal issues in this study. The results of this study found that investor protection against insider trading in the Indonesian capital market has been provided, namely in Law Number 8 of 1995 concerning Capital Markets (Capital Market Law) and its derivative regulations regulating the prohibition of insider trading. However, technical verification arrangements for insider trading actors in the Indonesian capital market, until now there have been no specific provisions related to technical verification for insider trading players in the Indonesian capital market, this makes it difficult to prove the existence of insider trading in Indonesia.